(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2019)
Introduction: Tuberculosis of short tubular bones of hand and foot is called tuberculousdactilitis or “spinaventosa”. This is uncommon type of osteoarticular tuberculosis more often seen in children than adults. This report describes tuberculosis affecting third metacarpal bone in a 25-year-old male patient presenting with a firm, painless, progressively increasing swelling over the dorsum of left hand. Diagnosis was made by cytological examination of aspirate from the affected area.